Variation in Symbiodinium ITS2 sequence assemblages among coral colonies - Stat, Michael; Bird, C.; Pochon, X.; Chasqui, L.; Chauka, L.; Concepcion, G.; Logan, D.; Takabayashi, M.; Toonen, R.; Gates, R. (2011)
Endosymbiotic dinoflagellates in the genus Symbiodinium are fundamentally important to the biology of scleractinian corals, as well as to a variety of other marine organisms. The genus Symbiodinium is genetically and functionally diverse and the taxonomic nature of the union between Symbiodinium and corals is implicated as a key trait determining the environmental tolerance of the symbiosis. Surprisingly, the question of how Symbiodinium diversity partitions within a species across spatial scales of meters to kilometers has received little attention, but is important to understanding the intrinsic biological scope of a given coral population and adaptations to the local environment. Here we address this gap by describing the Symbiodinium ITS2 sequence assemblages recovered from colonies of the reef building coral Montipora capitata sampled across Kane'ohe Bay, Hawai'i. A total of 52 corals were sampled in a nested design of Coral Colony(Site(Region)) reflecting spatial scales of meters to kilometers. A diversity of Symbiodinium ITS2 sequences was recovered with the majority of variance partitioning at the level of the Coral Colony. To confirm this result, the Symbiodinium ITS2 sequence diversity in six M. capitata colonies were analyzed in much greater depth with 35 to 55 clones per colony. The ITS2 sequences and quantitative composition recovered from these colonies varied significantly, indicating that each coral hosted a different assemblage of Symbiodinium. The diversity of Symbiodinium ITS2 sequence assemblages retrieved from individual colonies of M. capitata here highlights the problems inherent in interpreting multi-copy and intra-genomically variable molecular markers, and serves as a context for discussing the utility and biological relevance of assigning species names based on Symbiodinium ITS2 genotyping. © 2011 Stat et a.l.